Simulation and Characterization of Macro-Nutrient Deficiency Symptoms of Abaca (Musa textilis Née var. Inosa) Grown Using Nutrient Film Technique (NFT) - Rosit, James Francienne J.; Armecin, Romel B.; Belarmino, Marilyn M.; Benitez, Marilou M.; Cuadra, Lijueraj (Future Science / FSH-PH Publications, 2025)
This study was conducted in order to determine the effects of macronutrient deficiency to the morpho-physiological and biochemical properties of abaca. Randomized Complete Block Design was used in the study with three nutrient omissions (N, P & K) replicated three times with 12 samples per treatment replicate. This was conducted at the National Abaca Research Center screenhouse, Visayas State University, Baybay City, Leyte. Abaca under N and K deficiency produces the shortest plant height, pseudostem length, pseudostem girth, leaf length and leaf width. N deficient plant produces the smallest total leaf area while P deficient plants reduce pseudostem length and leaf width of abaca. However, P deficient plants showed comparable effects to the plant height, pseudostem girth, leaf length and total leaf area of abaca plants with complete nutrients. Furthermore, chlorophyll a and chlorophyll b content of abaca was lowest under N deficiency while control, P and K deficient plants showed comparable results. Free radical scavenging activity was also lowest under N and K deficient plants. Stomatal aperture was lowest under N, P & K deficient plants while P deficiency decreases stomatal length. These results suggests that abaca is more sensitive to N and K deficiency as most of the morpho-physiological and biochemical properties of abaca was significantly reduced under these conditions.